Partition-Based RIS-Assisted Multiple Access: NOMA Decoding Order Perspective - Kim, Yonghwi; Kim, Jae Hyun; Chae, Chan Byoung (IEEE Transactions on Vehicular Technology, 2022)
In this correspondence, we propose a closed-form resource allocation called partition-based multiple access (MA), which simultaneously utilizes both a reconfigurable intelligent surface (RIS) and non-orthogonal multiple access (NOMA) to reduce processing overhead and transmit power. The RIS can tune the mmWave signal and reduce the downlink transmit power, and NOMA achieves a relatively higher spectral efficiency than other MA methods. The integration of the RIS and NOMA, thus, can be a powerful solution. Previous studies have yet to obtain a closed-form solution for both the beam tuning settings and the decoding order in low complexity in the conventional RIS-NOMA. The proposed partition-based MA method, however, divides and arranges the array elements of the RIS to generate a fine beam for NOMA communications. We compare the transmit power reduction of the proposed method with the transmit power reduction of time-sharing and decode-and-forward relay. To confirm the feasibility of the integration, we also derive the criteria for MA mode selection.
Keywords: Complexity theory; Multiple access; Non-orthogonal; Non-orthogonal multiple access; Reconfigurable; Reconfigurable intelligent surface; Relay; Symbol; Tuning; multiple access; non-orthogonal multiple access (NOMA); Reconfigurable intelligent surface (RIS)